The Effect of Peer Teaching Methods on Results of Learning Writing Negotiation Text (Sains Humanika, 2020)
This istudy iaims to idetermine the ieffect of peer teaching learningi methods on learning outcomes of negotiating text writing skills. This study is a true experimental design study aimed to idetermine the ieffect iof peer teaching learning imethods on ilearning ioutcomes of the writing ability of negotiating students in class X MA Aisyiyah Sungguminasa 2018/2019 academic year. The iresearch idesign iused was a ipretest-posttest icontrol igroup idesign. The studyipopulation iwas alliof MA Aisyiyah Sungguminasa students consisting of six classes. Samples were obtained using purposive sampling technique and selected Science iclass Xi as the experimental iclass and Social iclass X as a control iclass with the number of students respectively 24 and 29 students. The experimental class was taught using the peer teaching method, while the control class was without using the peer iteaching imethod. The iindependent variable in thisi studyi is the peer teachingi method, and the dependent variable is the learning outcome of students' negotiating writing ability. Data collection techniques used test techniques taken from the results of the posttest and observations of students' activities on the application of the method. Inferential statistical analysis results prove that the data are normally distributed and homogeneous. Hypothesis testing carried out by t-testi resulted in a t-counti of 872.5 which was then compared with a t-tablei of 2.007 or t-counti > t-tablei which means that H0 iwas rejectedi and H1 was iaccepted. An alternative hypothesis (H1) is accepted if the value of it-count > t-table. It can be concluded that the method of peer teaching affects the learning outcomes in the negotiation imaterial of iclass X MA Aisyiyah Sungguminasa.
Keywords: Peer teaching methods; writing negotiating texts; Indonesian learning outcomes